Online Learning Through Google Classroom: Effects on Students Critical Thinking Skills in Chemistry - Khezel Jean F. Sombria; Diane L. Celestial; Clea Grace M. Jalagat; Anamarie G. Valdez (ASEAN Journal of Science and Engineering Education, 2023)
This study determined the effectiveness of the self-learning module and online learning through google classroom in the improvement of grade 9 students' critical thinking skills in chemistry. This study employed the experimental research design to the identified grade 9 students of two public schools, in which the test was done from 2020 to 2021 using a purposive sampling technique. Findings revealed that the level of critical thinking skills in problem-solving of students who are exposed to online learning through google classroom is higher than those of students who are exposed to self-learning modules. On the other hand, both methods of learning resulted in an average in the level of critical thinking skills in the Analysis of students with the online learning through google classroom gained a higher mean compared to that with the self-learning module. The study also revealed that there was a significant difference between problem-solving and analysis of critical thinking skills of the self-learning module and online learning through google classroom. The level of critical thinking skills in students' learning increases as they used online learning compared to the modular approach.